Aggression, self-control, life satisfaction, and resilience as predictors of mental health in Brazilian jiu-jitsu athletes - de Lorenco-Lima, Leandro; Gaines, Stacey A.; Waterbury, Elisabeth M. (Frontiers in Sports and Active Living, 2025)
IntroductionBrazilian jiu-jitsu has been discussed as an effective type of psychosocial therapy, with the social interactions within the Brazilian jiu-jitsu community serving as a buffer against mental health disorders. However, the psychological variables associated with optimal mental health in Brazilian jiu-jitsu have yet to be explored. This study examined the extent to which resilience, grit, self-efficacy, self-control, aggression, and life satisfaction (IVs) could predict mental health in male and female Brazilian jiu-jitsu athletes.MethodsThe sample included 420 athletes, representing 331 males (78.8%) and 89 females (21.2%) from 18 to 60 years of age (38.2 ± 8.8), who responded to training-related questions followed by the Mental Health Disorders Screening Instrument for Athletes, Brief Resilience Scale, Grit Scale, General Self-Efficacy Scale, Brief Self-Control Scale, Brief Aggression Questionnaire, and Satisfaction with Life Scale.ResultsIn males, results revealed that a multiple linear regression was statistically significant, with the IVs accounting for approximately 51.7% of the variance in mental health disorders. Aggression (9.1% variance), self-control (7.3% variance), life satisfaction (5.0% variance), and resilience (1.2% variance) were significantly associated with mental health disorders in male athletes. In females, a multiple linear regression was statistically significant, with the IVs accounting for approximately 45.3% of the variance in mental health disorders. Aggression (6.0% variance), and life satisfaction (3.0% variance) were significantly associated with mental health disorders in female athletes.ConclusionIn conclusion, male Brazilian jiu-jitsu athletes presenting higher self-control, life satisfaction, and resilience, and lower aggression, and female athletes presenting higher life satisfaction and lower aggression were more likely to present better mental health than athletes with opposing characteristics. With the rising popularity of Brazilian jiu-jitsu, these findings may inform clinical professionals when developing treatment plans to address mental health in athletes in this population.